2016
DOI: 10.1158/1078-0432.ccr-15-1745
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of BKM120 (Buparlisib) in Combination with Fulvestrant in Postmenopausal Women with Estrogen Receptor–Positive Metastatic Breast Cancer

Abstract: Purpose This trial was conducted to determine the maximum tolerated dose (MTD) and preliminary efficacy of buparlisib, an oral pan-class I PI3K inhibitor, plus fulvestrant in postmenopausal women with metastatic estrogen receptor positive breast cancer (ER+BC). Experimental Design Phase IA employed a 3+3 design to determine the MTD of buparlisib daily plus fulvestrant. Subsequent cohorts evaluated intermittent (5 of 7 day dosing) and continuous buparlisib (100mg daily). No more than 3 prior systemic treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…The overall safety profile (elevated liver enzymes, rash, hyperglycaemia, psychiatric disorders [i.e. depression and anxiety]) was consistent with that expected for buparlisib [2224,26,36]. However, the frequency of these in this study was much higher than previously reported [26,37].…”
Section: Discussionsupporting
confidence: 89%
“…The overall safety profile (elevated liver enzymes, rash, hyperglycaemia, psychiatric disorders [i.e. depression and anxiety]) was consistent with that expected for buparlisib [2224,26,36]. However, the frequency of these in this study was much higher than previously reported [26,37].…”
Section: Discussionsupporting
confidence: 89%
“…In a phase I trial of the pan-PI3K inhibitor, buparlisib, an intermittent five days on, two days off schedule produced fewer early onset adverse events, at the same daily dose of buparlisib (Ma et al, 2016). Intermittent dosing may also permit more pronounced pathway inhibition with equivalent toxicity for less toxic inhibitors such as the isoform-selective PI3K inhibitors.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…Another phase 1 study evaluated buparlisib in combination with fulvestrant demonstrating antitumor activity in 31 patients with HR+ MBC with a CBR of 58.6%. Also in this case, response was not associated with PIK3CA mutation; however, loss of PTEN, PR expression, or mutation in TP53 was most common in resistant cases, and mutations in AKT1 and ESR1 did not preclude treatment response [70]. The MTD of buparlisib was confirmed at 100 mg daily even with fulvestrant.…”
Section: Buparlisib (Bkm120)mentioning
confidence: 64%